My Aunt Sally, or, 'our' Keynes and the varieties of Keynesianism. (July 2016) - Mann, Geoff
Unable to properly address the full range of insight provided in the responses to 'Keynes resurrected?' in this reply I try to explain my motivations for the paper and situate its (several) problems in that larger context. I also speak specifically to the questions of Keynesianism's relation to neo-liberalism, to 'deep democracy', and to the limited political horizons suggested by the territorial imaginary that arguably underwrites the original article. I also try to better justify my claim that 'Keynes is our Hegel', by linking Keynesian reason to a broader intellectual and historical trajectory.